Defibrillation pad placement accuracy among Advanced Life Support instructors: A manikin-based observational study examining experience, self-evaluation, and actual performance - Dennie Wulterkens; Freek Coumou; Cornelis Slagt; Reinier A. Waalewijn; Lars Mommers (Resuscitation Plus)
Background: Ventricular fibrillation is common in patients with out-of-hospital cardiac arrest. Early and effective defibrillation is important for their survival. Effective defibrillation depends highly on correct positioning of the defibrillation pads. Teaching this correctly by ALS instructors is therefore crucial. Methods: Fifty certified advanced life support instructors were recruited from a large training institute. Participants were asked to place defibrillation pads on an anatomically and real-weight (90 kg) manikin. Primary outcome was the placement of defibrillation pads placed in the sternal-apical and anterior-posterior positions. Secondary outcomes were performance self-assessment, defibrillation experience, self-perceived competence and self-efficacy in teaching defibrillation. These measures were evaluated using an 11-point Likert scale. Results: A total of 31 medical doctors and 19 registered nurses were enrolled in this study. Defibrillation pads were placed (mean ± SD) 42 ± 21 mm, 38 ± 23 mm, 35 ± 19 mm and 61 ± 48 mm from the reference point for the sternal, apical, anterior and posterior pads respectively, resulting in a respectively correct placement of 18%, 20%, 32% and 28%. The average number of correctly applied pads per instructor was 0.98 ± 0.74 out of four.Self-assessment of defibrillation pads placed by the participants were 8.56 ± 1.33 and 7.88 ± 1.64 for the sternal-apical and anterior-posterior positions respectively. Personal defibrillation experience showed that the majority had applied over 20 standard defibrillations. Experience with anterior-posterior pad placement was less and experience with bi-axillary and double sequential external defibrillation positions were absent in most participants. Self-perceived competence for the sternal-apical, anterior-posterior, bi-axillary and dual external synchronized positions were 8.68 ± 1.06, 8.08 ± 1.37, 5.57 ± 2.95 and 5.11 ± 2.67 respectively. Self-efficacy score for teaching defibrillation was 8.59 ± 0.81. No association was found between the number of correctly applied pads and any of the participants’ variables. Conclusion: This study corroborates and expands upon existing knowledge regarding the challenges of defibrillator pad placement, revealing substantial variation in placement accuracy among instructors. Our novel analysis of pad angles and anterior-posterior analysis demonstrates that a significant portion of pads are incorrectly placed. These findings highlight the need for standardized approaches and improved training methodologies in defibrillator pad placement.